Case Report: Dyke-Davidoff-Masson syndrome resulting from a rare combination of hypoplastic left posterior cerebral artery and ipsilateral fetal-type posterior communicating artery - Huang, He; Wang, Chunyu; Hua, Huijuan; Zhang, Yingju; Zhao, Bo; Wan, Dongjun (Frontiers in Human Neuroscience, 2025)
IntroductionDyke-Davidoff-Masson syndrome (DDMS) is a rare neurological disorder characterized by unilateral hemiparesis, facial asymmetry, severe epilepsy, and intellectual disability. While congenital DDMS is predominantly attributed to anterior circulation anomalies [e.g., internal carotid artery (ICA) or middle cerebral artery (MCA) hypoplasia], posterior circulation involvement remains unreported. Here, we present the first documented case of congenital DDMS resulting from a rare combination of hypoplastic left posterior cerebral artery (PCA) and ipsilateral fetal-type posterior communicating artery (FTP).Case presentationA 19-year-old male exhibited atypical DDMS manifestations: absence seizures, preserved motor function, and occipitotemporal cognitive deficits (MoCA: 20/30). Neuroimaging revealed classic DDMS features. Angiography confirmed left PCA hypoplasia with FTP persistence, while CT perfusion demonstrated chronic left PCA hypoperfusion. Lamotrigine (100 mg/day) and regular cognition rehabilitative training resulted in good symptom control.ConclusionThis case identifies PCA hypoplasia with FTP as a novel DDMS etiology, challenging the MCA/ICA-centric paradigm. The “posterior phenotype” (absence seizures, preserved motor function, occipitotemporal cognitive deficits) expands DDMS heterogeneity. Multimodal imaging (angiography/perfusion) is diagnostic gold-standard, while personalized therapy optimizes outcomes.